QTL mapping for capsaicin and dihydrocapsaicin content in a population of Capsicum annuum 'NB1' × Capsicum chinense 'Bhut Jolokia'. Issue 3 (18th March 2016) - Lee, Jundae; Park, Seok Jin; Hong, Sun Chul; Han, Jung‐Heon; Choi, Doil; Yoon, Jae Bok
Abstract: Capsaicinoids are pungent compounds used for industrial and medical purposes including food, medicine and cosmetics. The Indian local variety 'Bhut Jolokia' ( Capsicum chinense Jacq.) is one of the world's hottest chilli peppers. It produces more than one million Scoville heat units (SHUs) in total capsaicinoids. In this study, our goal was to identify quantitative trait loci (QTLs) responsible for the high content of capsaicin and dihydrocapsaicin in 'Bhut Jolokia'. Capsicum annuum 'NB1', a Korean pepper inbred line containing 14 000 SHUs, was used as a maternal line. An F2 population derived by crossing between 'NB1' and 'Bhut Jolokia' was generated to map QTLs for capsaicinoids content. A total of 234 markers, including 201 HRM, 21 SSR, 2 CAPS and 10 gene‐based markers of the capsaicinoid synthesis pathway, were mapped. The final map covered a total distance of 1175.2 cM and contained 12 linkage groups corresponding to the basic chromosome number of chilli pepper. Capsaicin and dihydrocapsaicin content were analysed in 175 F2 pepper fruits using the HPLC method. The maximum total capsaicinoids content was 1389 mg per 100g DW (dry weight), and the minimum content was 11 mg per 100g DW. Two QTLs ( qcap3.1 and qcap6.1 ) for capsaicin content were identified on LG3 and LG6, and two QTLs ( qhdc2.1 and qdhc2.2 ) for dihydrocapsaicin content were located on LG2. We did not detect QTLs for total capsaicinoids content. The QTL positions for capsaicin content were different from those for dihydrocapsaicin content. These results indicate that the complexity of selecting for more pungent chilli peppers must be considered in a chilli pepper breeding programme. The QTL‐linked markers identified here will be helpful to develop more pungent pepper varieties from 'Bhut Jolokia', a very hot pepper.